Understanding of Anion Transport in Polymer Electrolytes for Supercapacitors. Issue 2 (30th November 2018) - Li, Tong; Hu, Jingzhi; Wei, Bingqing
Abstract: Polymer electrolytes are critical to solid‐state energy storage devices because of their electrical/mechanical/thermal stability. The energy storage mechanisms of supercapacitors call for a higher degree of anion transports in the polymer electrolytes. Therefore, the improvement of anions transport is critical to the performance of supercapacitors. However, the underlying transport mechanisms of different anions in the polymer electrolyte system has rarely been studied. In the present study, by molecular modeling, it is understood and demonstrated that different anions adapt to different transfer mechanisms in the polymer electrolytes during the charging/discharging process, allowing one to tune the anion transport by either adjusting the polymer structures or change the anion types. For the H2 SO4 ‐poly(vinyl alcohol) (PVA)‐based system, the diffusion of anions is more significant, while the H3 PO4 ‐PVA system relies on the alignment of anions to the electrical field. The fundamental understanding will guide polymer electrolyte design for the solid‐state energy storage devices. Abstract : The strategy of tuning anion conductivity in different energy storage devices varies according to the content of polymer electrolytes . Sulfuric‐acid‐based electrolytes employ the transportation of anions to store electrical potential while Phosphoric‐acid‐based electrolytes employ dipole moments to stores the energy. This difference calls for the careful selection of anions in the design of high‐efficiency supercapacitors.